READING FOR SPECIFIC INFORMATION - Abduolimova Maftuna Nurulloxon qizi; Sobirova Niginabonu Nodirjon qizi (TADQIQOTLAR, 2025)
Abstract: In a world where texts overflow and attention fades quickly, the ability to read with purpose becomes a silent superpower. This paper explores reading for specific information not merely as a strategy, but as an intellectual shortcut — a skill that turns chaos into clarity. Rather than passively consuming paragraphs, the reader transforms into a seeker, scanning the landscape of words with intent. Through theoretical reflection and practical relevance, this article highlights how mastering this subtle art can reshape one’s relationship with information, from academic studies to everyday decisions.